Analysis of the spatiotemporal dynamics of vascular injury and regeneration following experimental Spinal Cord Injury - Christian J. Entenmann; Emily J. von Bronewski; Lilly Waldmann; Lea Meyer; Katharina Kersting; Laurens T. Roolfs; Lasse M. Schleker; Melina Nieminen-Kelhä; Irina Kremenetskaia; Frank L. Heppner; Michael G. Fehlings; Peter Vajkoczy; et al. (Brain and Spine)
Introduction: The loss of vasculature in Spinal Cord Injury (SCI) contributes to secondary injury, expanding the injury to unharmed spinal cord (SC) regions. Understanding these mechanisms is crucial for developing therapeutic interventions. Research question: Comprehensive analysis of the temporospatial dynamics of vascular injury and regeneration following SCI. Materials and methods: Adult C57BL/6J mice were subjected to clip-compression SCI (Th 6/7, 5g, 60s, n = 20) or sham injury (laminectomy, n = 4), and sacrificed at 1, 3, 7, 14, and 28 days (d) post-injury following intracardial fluorescein isothiocyanate (FITC)-Lectin perfusion. Histological analysis (CD31, FITC-Lectin, Ki-67, IgG, TER-119) assessed vascular changes, permeability, and proliferation within the injury epicenter (region 0 (R0), ± 0,5 mm) and two adjacent SC regions (R1: ± 1 mm, R2: ± 2.5 mm). Results: Perfusion loss (FITC-Lectin+/CD31+), was most severe in R0 and R1 at d3 (p < 0.01). Significant vascular loss in R2 started at d3 (p = 0.043). Perfusion was restored at d28 in R0 and R1, and at d7 in R2. Vessel density (CD31+) returned to baseline quicker (R0: d3, R1 and R2: d14). Vascular proliferation (CD31+/Ki-67+) manifested across all regions at d3 (p < 0.01), and most notably in R2 (p < 0.01). Vascular permeability for IgG remained disrupted until d3 in R0 and R1 and until d14 in R2. Discussion and conclusion: Vascular injury is most severe initially and spreads to the surrounding SC regions. Gradual vascular regeneration occurs early and up to a considerable distance from the injury epicenter, highlighting the potential of early therapeutic interventions targeted at vascular repair and regeneration.